Using Nonadditive Fuzzy Integral to Assess Performances of Organizational Transformation Via Communities of Practice - Chu, Mei-Tai; Shyu, Joseph Z.; Tzeng, Gwo-Hshiung; Khosla, Rajiv (IEEE transactions on engineering management, 2007)
Organizational transformations have been widely adopted by firms who wish to improve their competitive advantage to be better prepared to face external challenges. This research has chosen Communities of Practice (CoPs) as the subject of discussion for an assessment model to reform organizations that undertake CoPs for collective knowledge to enhance their core competencies. Given the interrelationships between criteria, this research uses the nonadditive fuzzy integral to develop a framework for the CoPs performance assessment. The purposes of this paper are to identify the key dimensions/criteria in the CoPs, to use fuzzy logic method to analyze the relative importance of each criterion, and to rank the criteria so that proper resources can be allocated while managing the CoPs. Through interviews with experts, four strategy alternatives and 16 criteria along four dimensions are generated. A survey of the CoPs practitioners is then conducted to compare the results of each criterion. The results will not only help organizations that intend to initiate changes via the CoPs activities to decide the ranking of their appraisal criteria, but it can also assist them in guiding the behavior of their staff while effectively monitoring and improving the performances of the CoPs.